PENYULUHAN PEMASARAN BENUR UDANG VANAME (Litopenaeus vannamei) HASIL PANTI PEMBENIHAN SKALA RUMAH TANGGA (HSRT) DI DUSUN KEMBANGSAMBI, DESA PASIRPUTIH, KECAMATAN BUNGATAN - Musyaffa Rafiqie (LP2M Universitas Ibrahimy, 2021)
The purpose of marketing counseling for whiteleg shrimp seeds (Litopenaeus vannamei) from a household scale hatchery (HSRT), Kembangsambi, Pasir Putih, Bungatan was to motivate and to provide information about the marketing of whiteleg shrimp seeds. Activity method which is used to solve the problems mentioned above is marketing counseling for whiteleg shrimp seeds. This activity includes the material for marketing counseling activities, taxonomy of whiteleg shrimp, marketing concept with planning strategy, and marketing mix. The results of this counseling activity are the farmers will be able to maintain the marketing of whiteleg shrimp seeds, will be able to apply the marketing concept with strategic planning for whiteleg shrimp seeds, and will be able to apply the marketing mix for the marketing of whiteleg shrimp seeds so that it will increase economic growth in the Situbondo Regency and in particularly improve the household economy.